The impact of digital literacy on farmland scale operations:exploring the mediating and moderation roles of land transfer and land dependence - Lulu Yang; Song Yu; Song Yu; Bin Liu (Frontiers in Sustainable Food Systems)
IntroductionAgricultural scale operation serves as a crucial avenue for advancing the construction of agricultural modernization and fostering the development of a formidable agricultural nation. It is important to note that agricultural scale operation underscores not only the expansion of land acreage but also the contiguous and integrated management of land parcels.MethodsThis study utilizes data from the 2020 Chinese Academy of Social Sciences rural revitalization research to assess farmers' digital literacy levels through factor analysis and principal component analysis. After elucidating the underlying logic of how digital literacy influences the scale of agricultural land operations, we employ linear regression models, mediated moderation models, and other statistical tools to delve into the specific impacts of farmers' digital literacy on their farmland scaling behaviors.ResultsThe findings reveal that: (1) Digital literacy exerts a positive effect on the scale of farmland management undertaken by farmers. Specifically, for every unit increase in farmers' digital literacy, there is an average corresponding increase of 0.811 units in the overall scale of farmland management, 0.454 units in plot size, and 0.633 units in land concentration, respectively. (2) Mechanism testing reveals that an enhancement in farmers' digital literacy facilitates farmland transfers, thereby promoting large-scale farmland operations. Additionally, farmers' land dependence amplifies the positive effect of digital literacy on such operations. (3) Sub-dimension analysis yields further insights: In the realm of digital access, improved digital media literacy encourages farmers to consolidate their land holdings, expand production scales, harness economies of scale, and ultimately boost agricultural production efficiency. Within the digital application dimension, heightened levels of digital business literacy and digital information literacy among farmers spur the expansion of their land operation scales and increase land concentration. Conversely, elevated digital social literacy and digital problem-solving literacy primarily drive the expansion of land operation scales but exert minimal influence on land concentration. (4) Heterogeneity analysis uncovers variations in the impact of farmers' digital literacy on farmland scale operation behavior across different human capital levels, age groups, and urban-rural contexts.DiscussionConsequently, to foster farmland scale operations, it is imperative to: Promote the development of rural digital infrastructure to enhance farmers' digital accessibility. Strengthen the factor market system to facilitate efficient circulation of various factors. Increase support for farmer benefits and assistance programs to bolster their risk resilience. Intensify skills training for farmers to activate their intrinsic motivations as primary actors in this process.